Sampoerna Retail Community Strategy in Developing Grocery Stores (Case Study: Paguyuban Src Curup Bersatu) - Dedy Juniansyah Pratama; Yudi Irawan Abi; M. Rahman Febliansyah (Social Sciences Journal, 2026)
Partnership and MSME Development Program Linking Concrete Strategies Implemented by SRC. The existence of SRC (Sampoerna Retail Community), this association guides partnerships between Sampoerna and conventional retailers to develop their businesses and reach to attract customers. This study aims to identify and analyze the strategies implemented by Sampoerna Retail Community (SRC) in developing grocery store businesses within the Paguyuban SRC Curup Bersatu. The analytical method used is qualitative data analysis, conducted interactively and continuously until data saturation is achieved, through three main stages: Data Reduction, Data Presentation, and Conclusion Drawing. Based on the research findings, it is proven that the Sampoerna Retail Community (SRC) strategy in developing grocery store businesses in Paguyuban Curup is carried out by focusing on Business Performance (increasing sales, store arrangement based on RBT principles), Community Development (establishing connections among traders to mutually develop their businesses), and Technology (utilization of digital features). For the Sampoerna Retail Community (SRC) strategy in developing grocery store businesses in Paguyuban Curup Bersatu to run effectively, supporting factors must be considered, namely: cooperation among multiple parties, the willingness of grocery store owners to progress, and the presence of digital innovation. Meanwhile, factors hindering the development of Paguyuban SRC Curup Bersatu include the limited number of participants and the community's lack of knowledge regarding the Ayo Kelontong application, a digital innovation by Sampoerna Retail Community (SRC).